2016
DOI: 10.1002/psp.2036
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internal Migration on Population Redistribution: an International Comparison

Abstract: We know that internal migration shapes human settlement patterns, but few attempts have been made to measure systematically the extent of population redistribution or make comparisons between countries. Robust comparisons are hampered by limited data access, different spacetime frameworks, and inadequate summary statistics. We use new analysis software (IMAGE Studio) to assess the effects of differences in the number and configuration of geographic zones and implement new measures to make comparisons across a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(154 citation statements)
references
References 33 publications
5
146
0
3
Order By: Relevance
“…Further research is required using countries where data are available on migration at different spatial scales to compare published rates with estimated means derived using the IMAGE Studio from configurations based on lower level spatial units. Whilst the results of the IMAGE project have reported the use of the Studio for comparative analysis of internal migration in different countries around the world (Bell et al 2015b;Rees et al 2016;Stillwell et al 2016) where zone systems are very different, there is also the potential in using the Studio to explore how scale and zonation effects might vary by demographic (age, sex, ethnicity) or socio-economic (occupation, tenure, health status) group in any single country (see Stillwell et al 2018, for an initial study of variations by age group in the UK). A further avenue of investigation might be to explore the relationship between migration indicators and explanatory variables at different spatial scales using correlation analysis of the type that was employed to investigate the MAUP effects in earlier studies of stock variables.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research is required using countries where data are available on migration at different spatial scales to compare published rates with estimated means derived using the IMAGE Studio from configurations based on lower level spatial units. Whilst the results of the IMAGE project have reported the use of the Studio for comparative analysis of internal migration in different countries around the world (Bell et al 2015b;Rees et al 2016;Stillwell et al 2016) where zone systems are very different, there is also the potential in using the Studio to explore how scale and zonation effects might vary by demographic (age, sex, ethnicity) or socio-economic (occupation, tenure, health status) group in any single country (see Stillwell et al 2018, for an initial study of variations by age group in the UK). A further avenue of investigation might be to explore the relationship between migration indicators and explanatory variables at different spatial scales using correlation analysis of the type that was employed to investigate the MAUP effects in earlier studies of stock variables.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable effort has been spent on constructing a global inventory of internal migration data sources (Bell et al 2015a) and creating a repository of migration and related (boundary and population) data sets ). The IMAGE project had a number of objectives that derive from analysis of the data sets held in the repository, including the comparison of overall migration intensities in countries for which data are available or can be estimated (Bell et al 2015b), the distances over which people migrate and the frictional effect of distance on migration ) and the impact of migration on population distributions in different countries (Rees et al 2016).…”
Section: Image Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of a rapidly ageing population (Giannakouris, 2008), migration becomes an increasingly important factor of population change (Findlay and Wahba, 2013); David Coleman (2006) goes as far as proposing the concept of the Third Demographic Transition, in which migration plays the key role as a factor of population replacement. While more public attention is fixed upon international migration (Van Wissen, 2001;Czaika and Haas, 2014), internal migration is crucial in determining sub-national population structures (Rees et al, 2013(Rees et al, , 2017. And the key distinction in the relative speed of population ageing at sub-national level is between urban and rural areas, which is in turn largely driven by migration, mostly internal .…”
Section: Introductionmentioning
confidence: 99%
“…But based on observations made in sub-Saharan Africa, where the DT process has taken place without the expected degree of economic development, it has been suggested that the underlying causes of fertility decline go beyond the state of a country's economy and wealth (Caldwell 1986;Caldwell and Caldwell 1987;Caldwell et al 1992;Bongaarts 2008;Shapiro and Gebreselassie 2008;Ezeh et al 2009;Bongaarts and Casterline 2012). The most commonly cited factors other than those directly related to economics are the education of women (e.g., Axinn and Barber 2001;Murtin 2012;Cuaresma et al 2014) and its influence on (societal) values and roles Korotayev et al 2016), urbanisation (Haggett 2001;Boquier et al 2011;Dyson 2011), and shifts in migration regimes (Rees et al 2016). Most recently, Wilson and Dyson (2017) proposed going beyond these rather conventional explanations to study the influence of a more comprehensive set of societal changes, including democratisation processes.…”
Section: Introductionmentioning
confidence: 99%